Bone microarchitecture and volumetric bone density impairment in young male adults with childhood-onset growth hormone deficiency. Issue 2 (February 2019) - Yang, Hongbo; Yan, Kemin; Yuping, Xu; Zhang, Qi; Wang, Linjie; Gong, Fengying; Zhu, Huijuan; Xia, Weibo; Pan, Hui
Abstract : Context: Adult growth hormone deficiency (AGHD) is characterized by low bone density and increased risk of fracture. Bone microarchitecture is insufficiently evaluated in patients with childhood-onset AGHD (CO AGHD). Objective: To assess volumetric bone density (vBMD) and bone microarchitecture in CO AGHD in early adulthood after cessation of recombinant growth hormone (rhGH) treatment. Design and subjects: Case–control study in a major academic medical center in Beijing, including 20 young male adults with CO AGHD and 30 age- and weight-matched non-athletic healthy men. High-resolution peripheral quantitative computerized tomography (HR-pQCT) of distal radius and tibia was performed. Outcomes: The main outcomes were vBMD and morphometry parameters from HR-pQCT. Results: Compared with healthy controls, CO AGHD group had significantly decreased insulin-like growth factor 1 (IGF-1) level and IGF-1 SDS ( P  < 0.001). β-CTX and alkaline phosphatase levels in CO AGHD group were significantly increased ( P  < 0.001). CO AGHD group had significantly decreased total vBMD, cortical vBMD, trabecular vBMD, cortical area, cortical thickness as well as trabecular thickness and trabecular bone volume fraction of both tibia and radius ( P  < 0.001). CO AGHD patients had an 8.4 kg decrease in grip strength and a significant decrease in creatinine levels ( P  = 0.001). At both tibia and radius, by finite element analysis, bone stiffness and failure load of the CO AGHD patients were significantly decreased ( P  < 0.001). After adjusting for age, BMI and serum levels of testosterone and free thyroxin, serum IGF-1 level was a positive predictor for total vBMD, cortical vBMD, cortical area, trabecular vBMD, bone stiffness and failure load of both tibia and distal radius in all subjects. Conclusions: Young adult male patients with childhood-onset adult growth hormone deficiency who are no longer receiving growth hormone replacement have prominently impaired volumetric bone density and bone microarchitecture and lower estimated bone strength.